2022
DOI: 10.14814/phy2.15294
|View full text |Cite
|
Sign up to set email alerts
|

Augmented muscle deoxygenation during repeated sprint exercise with post‐exercise blood flow restriction

Abstract: A number of teams and racket sports (e.g., soccer, basketball, and hockey) require the ability to perform repeated maximal sprints (<10 s) with a short recovery (<30 s). This ability is called as repeated-sprint ability (RSA) (Bishop et al., 2011;Girard et al., 2011). To improve RSA, repeated sprint-exercise (RSE) is recommended. Several previous studies reported that RSE increased maximal oxygen uptake ( V O 2peak ) and total work during the identical period of exercise, and improved muscle buffer capacity (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
3
10
2
Order By: Relevance
“…In this study BLa 2 was not different between the conditions. Unchanged BLa 2 between conditions is likely the result of RSE being completed at maximal intensity, and this observation is supported by recent research investigating leg or arm-cycling RSE with BFR that is volume equated (16,19) or completed to exhaustion (37)(38)(39). Similar BLa 2 was observed in all conditions despite lower mean power output during C-BFR and I-BFR REST than during Non-BFR.…”
Section: Discussionsupporting
confidence: 73%
“…In this study BLa 2 was not different between the conditions. Unchanged BLa 2 between conditions is likely the result of RSE being completed at maximal intensity, and this observation is supported by recent research investigating leg or arm-cycling RSE with BFR that is volume equated (16,19) or completed to exhaustion (37)(38)(39). Similar BLa 2 was observed in all conditions despite lower mean power output during C-BFR and I-BFR REST than during Non-BFR.…”
Section: Discussionsupporting
confidence: 73%
“…A study by Manimmanakorn et al (2013) demonstrated that low-loading resistant exercise combined with BFRT significantly improved 0–5m and 0–10 m sprint abilities in female netball players. Possible explanations for the improvement in sprint performance are related to positive muscle responses, leading to increasing lower-limb power output ( Doma et al, 2020 ; Ienaga et al, 2022 ). Metabolic accumulation (e.g., lactic acid) caused by restricting blood flow led to cell swell and promotes the secretion of growth hormone, resulting in increases in the muscle cross-sectional area and motor unit recruitment ( Takarada et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…These authors found significant increases in the expression of HIF-1α only in the L-IEH group. Ienaga et al 15 investigated the effects of L-IEH during an SIT training consisting of three sets of 6 s maximum sprints with 24 s rest between sprints and 5 min rest between sets. They found higher deoxyhaemoglobin and lower tissue saturation index (StO 2 ) in L-IEH.…”
Section: Local Inter-effort Recovery Hypoxiamentioning
confidence: 99%
“…An interesting approach between hypoxia and training refers to the addition of hypoxia during the inter-effort recovery (IEH) period through local blood flow restriction (local inter-effort recovery hypoxia (L-IEH)) 15 16 or by systemic hypoxia (systemic inter-effort recovery hypoxia (S-IEH)). 17 18 …”
Section: Introductionmentioning
confidence: 99%